Transforaminal Epiduroscopic Laser Ablation of Sinuvertebral Nerve in Patients with Chronic Diskogenic Back Pain: Technical Note and Preliminary Result - Kim, Hyeun Sung; Paudel, Byapak; Chung, Sung Kyun; Jang, Jee Soo; Oh, Seong Hoon; Jang, Il Tae (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2017)
Background Diskogenic back pain is an unsolved mystery and accounts for a large number of patients with chronic low back pain. Various treatment modalities have been described, but treatment is still a matter of debate. We evaluated transforaminal epiduroscopic laser ablation (TELA) focusing on sinuvertebral nerve laser ablation for chronic diskogenic back pain. To our knowledge this is the first treatment described for diskogenic back pain that directly targets the sensitized sinuvertebral nerve extradiskally through a transforaminal approach. Methods A total of 52 patients with a diagnosis of chronic diskogenic back pain and treated with TELA between September 2015 and June 2016 were analyzed. Outcome was measured with the visual analog scale (VAS), Macnab criteria, and Oswestry Disability Index (ODI).Results Of the 52 patients, 55.8% were female, and the mean age was 42.40 ± 11.99 years. Pfirrmann disk degeneration grade was mostly grade IV (63.5%) and involved spinal levels L4–L5 and L5–S1. The average follow-up period was 15.88 ± 1.79 months. VAS decreased significantly after TELA (p < 0.001). Improvement in ODI was also significant (p < 0.001). Good to excellent outcome was 96.1% according to the Macnab criteria. Four patients had transient motor weakness.Conclusion TELA targeting to the sinuvertebral nerve was effective in 96.1% with good to excellent results and an immediate decrease in chronic diskogenic back pain. The sinuvertebral nerve may play an important role in chronic diskogenic back pain.
Keywords: diskogenic back pain; sinuvertebral nerve; laser ablation; transforaminal epiduroscopic laser ablation